Application of switched-capacitor circuits to realization of neuron-like binary hamming classifier - Korzec, Zdzisław; Kacprzak, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, based on the literature and our own research, a concept of application of switched-capacitor circuits for designing neural networks with constant weights has been presented. The solution is attractive, especially in view of designing simple classifiers and pattern recognition systems implemented in a semiconductor very large scale technology (VLSI).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka